Analisis Kelayakan Bisnis Usaha Rumah Makan Utami - Wardoyo, Ainaya Aprilia; Siregar, Tianovia; Permas, Try Utami; Utami, Wita (Asosiasi Dosen Akuntansi Indonesia, 2023)
A business feasibility study is needed to see a picture of whether a business is feasible or not to be run. This study aims to see whether the Utami Restaurant business is feasible or not. Every aspect to be considered feasible must have a certain value standard, but the assessment is not only carried out on one aspect only. Assessment to determine eligibility must be based on several aspects. The analytical method used in the business feasibility study covers market and marketing aspects, technical aspects, financial aspects and sensitivity analysis which is used to test the impact of rising costs on the feasibility of the business. The results of this study found that the Utami Restaurant business is feasible to run and has very good prospects.